US Hegemony in Latin America: Think Tanks and the Formation of Consensus about the Chinese Presence - Wietchikoski, Luciana; Milani, Livia Peres [UNESP] (FapUNIFESP (SciELO), 2024)
In recent years, U.S. government agencies have defined the Chinese presence in Latin America as a challenge, which has organized foreign policy towards the region. Departing from a neo-Gramscian approach, this paper investigates the bibliographical production of U.S. think tanks and seeks to understand the construction of consensus about the Chinese presence in Latin America. The methodology is based on content analysis and we identified two main narratives: in the first, the Chinese presence is presented as a threat to U.S. regional hegemony; in the second, the Chinese adaptation to liberal precepts is sought. There are therefore nuances in how the Chinese power is perceived, although the discourses remain restricted to the promotion of capitalism and neoliberalism under U.S. leadership.
Keywords: Hegemony; Latin America; think tanks; U.S. foreign policy